NFIA-dependent upregulation of SMC4 promotes metastasis and metabolic reprogramming in glioma - Li, Guoyin; Zhao, Yukui; He, Yubo; Qian, Zhaoqiang; Li, Xiaoyan; Song, Zewen; Liu, Zhiqiang (Frontiers in Oncology, 2025)
BackgroundGliomas, particularly glioblastoma, are aggressive brain tumors with poor prognosis and unmet therapeutic needs. Structural maintenance of chromosomes 4 (SMC4), a core component of the condensin complex, is dysregulated in multiple cancers, but its role in glioma metabolism and metastasis remains unclear.MethodsUsing integrated multi-omics analyses of glioma datasets, we assessed SMC4 expression and its correlation with clinical outcomes. Functional studies in U-251MG and LN229 glioma cells including CCK-8, EdU, cell cycle, Transwell, and wound-healing assays were combined with subcutaneous xenograft and tail-vein metastasis mouse models to evaluate SMC4’s effects on proliferation, migration, invasion, and metastasis. ECAR/OCR and rescue experiments validated SMC4’s role in glycolysis. Luciferase reporter and ChIP assays identified nuclear factor I A (NFIA) as an upstream transcriptional regulator of SMC4. A prognostic model (SRRS) was developed via LASSO regression and validated across cohorts.ResultsSMC4 was significantly overexpressed in glioma tissues, with higher expression correlating with advanced tumor grades and poorer patient survival (AUC > 0.82). Mechanistically, SMC4 promoted G1/S cell cycle transition and proliferation in vitro/in vivo. It enhanced metastasis by activating TGF-β/SMAD signaling, evidenced by upregulated p-SMAD2/3, N-cadherin, SNAI1, and ZEB1, and increased lung metastases in mice. SMC4 also facilitated aerobic glycolysis by upregulating LDHA, shown via increased glucose uptake, lactate production, and ECAR, with rescue experiments confirming LDHA dependency. NFIA directly bound two motifs in the SMC4 promoter (-1379 bp and -354 bp), driving transcription, validated by dual-luciferase and ChIP assays. The SRRS, integrating 15 SMC4-coexpressed genes, stratified patients into high/low-risk groups with distinct survival (AUC > 0.7 for 1-, 3-, 5-year OS). A nomogram combining SRRS and clinical parameters improved accuracy (AUC > 0.88). Pharmacogenomic analysis linked SRRS to sensitivity to erlotinib and other agents.ConclusionSMC4 drives glioma progression through dual mechanisms TGF-β/SMAD-mediated metastasis and LDHA-dependent glycolysis regulated by NFIA. This extends beyond its known role in TGF-β activation by identifying NFIA as an upstream regulator and metabolic reprogramming as a novel function. The SRRS and nomogram provide robust tools for prognosis and personalized therapy, supporting the NFIA/SMC4 axis and downstream effectors as potential therapeutic targets for glioma.